Evolution of nutritional status and associated factors among formula-fed infants with cow's milk protein allergy in a government program - Giuliana Rizzo Taveira; Carolina Dadalto Rocha Fernandes; Yasmin Franco Rodrigues Silva; Maria Clara Barcelos de Aquino; Ana Carolina Menezes Vieira da Silva; Carolina Perim de Faria; Míriam Carmo Rodrigues Barbosa (BMC, 2023)
Abstract Background Cow's milk protein allergy (CMPA) is a common allergy in infants and can affect proper growth and development. This study verified factors associated with the evolution of the nutritional status (NS) among infants with CMPA fed with hypoallergenic formulas (HF). Methods This is a longitudinal study of infants (n = 1036) participating on a governmental program in Brazil. Researchers assessed Nutritional status before HF treatment (T1) and after HF treatment (T2). The causality of exposure variables on the evolution of NS was verified by Multinomial Logistic Regression (MLR). Results We observed an increase in anthropometric indexes analyzed with statistically significant results (p < 0.01). The weight/age and height/age scores showed a significant reduction in infants with nutritional deficit. The Body Mass Index (BMI) showed a decrease in the number of infants with nutritional deficit (< -2 z-score). On the other hand, there was an increase in those classified as at risk of overweight, overweight and obese. MLR showed that those who remained < 12 months in the program had a lower odds ratio (95% CI = 0.355-0.906; p = 0.018) to have inadequate NS with increasing BMI. Preterm infants were 4 times more likely (CI 95% = 1.520-10.694; p = 0.005) to have their BMI decreased and those who received nutritional counseling had a lower odds ratio (CI 95% = 0.411-0.953; p = 0.029) to maintain adequate NS. Conclusion The program has a significant impact on the NS of infants with CMPA. The constant management and implementation of differentiated criteria according to the evolution of NS for the supply of HF is fundamental in the continuity of this public policy.